Strategi School Branding Dalam Meningkatkan Manajemen Pemasaran Sekolah Pada Satuan Pendidikan Islam Swasta Di Kota Palangka Raya - Syarif, Ahmad Syarif; Fathul Zannah; Arna Purtina; Muqor Rama Hasanah (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to identify the school branding strategy used by private Islamic education units in Palangka Raya City in order to improve school marketing management. This research uses a qualitative method with a descriptive approach. Data collection techniques through observation, interviews and documentation. Data validation was carried out using the triangulation technique of data sources by comparing the results of observations, interviews and documentation with the theory used. The principal, deputy principal and teachers were used as informants. Data analysis through data collection, data reduction, data presentation and drawing conclusions. Research findings on School Branding strategies in improving school marketing management in private Islamic education units in Palangka Raya City which include creating jargon, institutional logos, vision and mission and all of this is displayed in printed or digital flayers, videos and photos on social media accounts and website management. It is hoped that the results of this research can provide references and information on improving School Branding strategies and fill in the gaps in Branding aspects that can still be implemented. Keywords. School Branding Strategy; Improving School Marketing